Temporal profiling of the breast tumour microenvironment reveals collagen XII as a driver of metastasis - Papanicolaou, Michael; Parker, Amelia L.; Yam, Michelle; Filipe, Elysse C.; Wu, Sunny Z.; Chitty, Jessica L.; Wyllie, Kaitlin; Tran, Emmi; Mok, Ellie; Nadalini, Audrey; Skhinas, Joanna N.; Lucas, Morghan C.; et al. (Nature communications, 2022)
The tumour stroma, and in particular the extracellular matrix (ECM), is a salient feature of solid tumours that plays a crucial role in shaping their progression. Many desmoplastic tumours including breast cancer involve the significant accumulation of type I collagen. However, recently it has become clear that the precise distribution and organisation of matrix molecules such as collagen I is equally as important in the tumour as their abundance. Cancer-associated fibroblasts (CAFs) coexist within breast cancer tissues and play both pro- and anti-tumourigenic roles through remodelling the ECM. Here, using temporal proteomic profiling of decellularized tumours, we interrogate the evolving matrisome during breast cancer progression. We identify 4 key matrisomal clusters, and pinpoint collagen type XII as a critical component that regulates collagen type I organisation. Through combining our proteomics with single-cell transcriptomics, and genetic manipulation models, we show how CAF-secreted collagen XII alters collagen I organisation to create a pro-invasive microenvironment supporting metastatic dissemination. Finally, we show in patient cohorts that collagen XII may represent an indicator of breast cancer patients at high risk of metastatic relapse. The distribution and organisation of matrix molecules in the tumour stroma help shape solid tumour progression. Here they perform temporal proteomic profiling of the matrisome during breast cancer progression and show that collagen XII secreted from CAFs provides a pro-invasive microenvironment.